The Voice of Indonesian EFL Students’: Mobile Learning Game Memrise to Boost English Speaking Skill - Wulandari, Shila Sandrina; Widiastuti, Oktavia; Liskinasih, Ayu (Journal of English for Academic and Specific Purposes (JEASP), 2025)
This study investigates the use of Memrise, a mobile learning game, to improve EFL students’ speaking performance in academic contexts. Grounded in gamification theory and interactionist theory, which explores how gamified vocabulary and pronunciation tasks could lead to speaking confidence and fluency. Qualitative descriptive research methods were used to thoroughly understand perspectives and points of view of the participants, consisting of thematically analyzed 20 multiple-choice and 6 interview questions. Seventeen Indonesian EFL students completed surveys and interviews. Results reveal that Memrise develops vocabulary retention, pronunciation, and motivation, though limitations persist in feedback mechanisms and academic speaking content. This study contributes to EAP digital pedagogy by providing qualitative insights of students who are unfamiliar with the app and answering how Indonesian EFL learners perceive the use of Memrise to boost speaking skills through academic speaking skill learning development. This study features direct opinions from Indonesian university education students—which is rarely covered in research—on how they use Memrise as a tool to learn speaking skills in an academic context. The findings suggest that while Memrise can facilitate foundational speaking practice and learner engagement, some limitations are found in its usage. Further adaptations are needed to maximize its relevance for academic speaking tasks in EFL classrooms.